A structural and mechanical analysis on PVD-grown (Ti,Al)N/Mo multilayers - Tavares, C. J. (2000)
(Ti,Al)N/Mo multilayered hard coatings have been designed to fulfil future applications concerning wear-prevention on tool steels. They have been deposited by reactive dc magnetron sputtering on high-speed steel substrates with modulation periods between 6.5 and 8 nm. Experimental X-ray diffraction (XRD), Rutherford backscattering spectrometry (RBS) and computational modelling of those patterns has undergone to survey structural properties such as modulation periodicity, interfacial roughness and density. Asymmetric XRD measurements confirmed that the textured grains, although being randomly distributed, possess a slight misorientation of ±11° due to their mosaic structure. Atomic force microscopy (AFM) analysis revealed a dome-rounded structure with columnar grain sizes between 90 and 120 nm in diameter, depending on deposition process parameters. The average ultramicrohardness of these multilayers can be as high as 36 GPa with a maximum Young's modulus of 445 GPa, while the adhesion critical load may reach 60 N.